Analysis model Model of Land Use Considering Different Scenarios in San Juan City, Argentina - Nieto, Patricia Lorena; Universidad Nacional de San Juan (Editorial Pontificia Universidad Javeriana, 2016)
San Juan defined is as a seismic oasis city with an intermediate scale. Hence, preserve land use and its occupation is very important from a sustainable point of view. This city has spread over the surrounding territory without proper land planning in the last 50 years. That situation has originated several environmental conflicts, such as the lack of green spaces in relation to population growth and the constructed area. Understanding this problem to predict future situations and evaluate different alternatives for land use is a complex work. Therefore, it uses system dynamics as an analysis methodology, also as valuable tool that helps manage this complexity. In order to obtain a first approximation model we consider the evolution of city population and the green areas, the number of homes and its variation in time. These parameters interact forming the analyzed system.